EXPOSURE RISK ASSESSMENT FOR HEAVY METALS WITH TOXIC POTENTIAL DISPERSED FROM THE COAL MATRIX INTO THE SOIL - Delia NICA - BADEA; Aniela BĂLĂCESCU (Fiabilitate şi Durabilitate)
The paper assesses the risk potential determined by the level of exposure to traces of heavy metals with toxic potential (Pb, Ni, Cd) from the soil, vegetation and grains adjacent to the area of exploitation and thermal energy processing of lignite. Average concentrations determined (mg.Kg -1 ): exceed normal values for soil for Pb (43.71) and Ni (64.14), do not show phytotoxic values for spontaneous vegetation and exceed the reference level for Pb and Cd in cereals according to current norms at European and World level. Taking into account exposure routes, exposure assessment parameters and average concentrations in soil and plants, have been estimated the individual risk for Ni, Cd and Pb. These individual risk index values in relation to the limit value WHO (10-6 ) demonstrated moderate potential impact on food safety and quality of life in this area.